2007
DOI: 10.1080/09540120600988517
|View full text |Cite
|
Sign up to set email alerts
|

The effects of individual- and community-level knowledge, beliefs, and fear on stigmatization of people living with HIV/AIDS in China

Abstract: This paper assesses the effects of individual- and community-level knowledge of HIV transmission, beliefs and fear of infection on individual attitudes toward and willingness to interact with people living with HIV/AIDS in China. Data are from a sample survey of 12,270 men and women age 15-49 from seven provinces/municipalities. The survey was conducted by the Population and Family Planning Commission in December 2003. Multilevel regression analyses show that stigmatization of people living with HIV/AIDS is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
7
20
0
Order By: Relevance
“…Another finding of this study is that children with better AIDS knowledge had less personal stigma toward PLWHA. The result is consistent with findings of other studies in China that have demonstrated the important role of improvement of AIDS knowledge in reducing stigma toward PLWHA (Chen, Choe, Chen, & Zhang, 2007;Lau & Tsui, 2005;Sullivan et al, 2010). The current study confirmed that dissemination of accurate AIDS knowledge may be important for the reduction of HIVrelated stigma among children.…”
Section: Discussionsupporting
confidence: 82%
“…Another finding of this study is that children with better AIDS knowledge had less personal stigma toward PLWHA. The result is consistent with findings of other studies in China that have demonstrated the important role of improvement of AIDS knowledge in reducing stigma toward PLWHA (Chen, Choe, Chen, & Zhang, 2007;Lau & Tsui, 2005;Sullivan et al, 2010). The current study confirmed that dissemination of accurate AIDS knowledge may be important for the reduction of HIVrelated stigma among children.…”
Section: Discussionsupporting
confidence: 82%
“…One of the reasons people hold negative attitudes toward PLWH is because of a low level of knowledge and frequent misconceptions about HIV infection. A survey of 12,270 persons in seven provinces in China showed that only 43% had accurate HIV knowledge (Chen, Choe, Chen, & Zhang, 2007). In Anhui province with one of the highest HIV prevalence rates in China, 17% of the rural residents had never heard of HIV or AIDS (Liu et al, 2006).…”
mentioning
confidence: 99%
“…However, it has been well established that HIV stigma and unfounded fears of contracting HIV significantly challenge the implementation of HIV programming in churches (Bluthenthal et al, 2012; Coleman, Lindley, Annang, Saunders, & Gaddist, 2012). Erroneous knowledge of HIV transmission, prevention, and treatment often perpetuated a perceived need for self-protection among religious groups that further excluded persons living with HIV/AIDS (Chen, Choe, Chen, & Zhang, 2007; Lew-Ting & Hsu, 2002; London & Robles, 2000; Takshashi, 1997). Studies, for example, have suggested a “co-occurrence” of correct and incorrect knowledge of HIV transmission and highlighted the importance of reinforcing knowledge of documented modes of transmission and correcting inaccurate transmission knowledge (Boer & Emons, 2004; London & Robles, 2000).…”
mentioning
confidence: 99%